2020
DOI: 10.1177/0196859920977122
|View full text |Cite
|
Sign up to set email alerts
|

Female Fashion as Leisure and Labor on Reddit

Abstract: This paper examines a vibrant online community called Female Fashion Advice, which exemplifies convergence culture because its members both produce and consume its content. This large subreddit offers a compelling alternative to traditional fashion journalism and empowers women to partake in a hobby that has been denigrated due to its association with femininity. Using grounded practical theory, we found that fashion is treated as serious leisure, as evidenced by displays of personal effort, career progress, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In his research on Digital Feudalism, Harrison (2021) claims that in attracting users to the prevalent private property of the present globalized internet, capital like Facebook and internet service providers have become voters of the land, putting account holders in the position of digital farmers and establishing a sort of digital feudalism that reveals itself in the exploitation of farmers yields, digital land lease collection, and tribute extraction. Similar research related to exploitation in other digital worlds (Murray & Desrayaud, 2021) who studied the dynamic online community Female Fashion Advice using a practical theory found that fashion is treated as a serious pastime, as evidenced by the personal endeavor, career advancement, and emphasis on lasting benefits. However, the women in the community are also struggling to keep the fashion industry from turning into unpaid labor.…”
Section: Introductionmentioning
confidence: 79%
“…In his research on Digital Feudalism, Harrison (2021) claims that in attracting users to the prevalent private property of the present globalized internet, capital like Facebook and internet service providers have become voters of the land, putting account holders in the position of digital farmers and establishing a sort of digital feudalism that reveals itself in the exploitation of farmers yields, digital land lease collection, and tribute extraction. Similar research related to exploitation in other digital worlds (Murray & Desrayaud, 2021) who studied the dynamic online community Female Fashion Advice using a practical theory found that fashion is treated as a serious pastime, as evidenced by the personal endeavor, career advancement, and emphasis on lasting benefits. However, the women in the community are also struggling to keep the fashion industry from turning into unpaid labor.…”
Section: Introductionmentioning
confidence: 79%
“…We extracted 3,788 posts and comments from the shortlisted online communities using R code using keywords such as "financial independence" or "FIRE," which align with similar research (Murray and Desrayaud, 2020). Several posts were excluded due to short length, irrelevant content and other criteria, resulting in 551 posts.…”
Section: Methodsmentioning
confidence: 99%